Stem Cells Grown in Osteogenic Medium on PLGA, PLGA/HA, and Titanium Scaffolds for Surgical Applications. (23rd December 2010) - Asti, Annalia; Gastaldi, Giulia; Dorati, Rossella; Saino, Enrica; Conti, Bice; Visai, Livia; Benazzo, Francesco
Abstract : Pluripotent adipose tissue-derived stem cells (hASCs) can differentiate into various mesodermal cell types such as osteoblasts, chondroblasts, and myoblasts. We isolated hASCs from subcutaneous adipose tissue during orthopaedic surgery and induced the osteogenic differentiation for 28 days on three different synthetic scaffolds such as polylactide-co-glycolide (PLGA), polylactide-co-glycolide/hydroxyapatite (PLGA/HA), and trabecular titanium scaffolds (Ti6Al4V). Pore size can influence certain criteria such as cell attachment, infiltration, and vascularization. The aim of this study was to investigate the performance of PLGA and PLGA/HA scaffolds with a higher porosity, ranging between 75% and 84%, with respect to Ti scaffolds but with smaller pore size, seeded with hASCs to develop a model that could be used in the treatment of bone defects and fractures. Osteogenesis was assessed by ELISA quantitation of extracellular matrix protein expression, von Kossa staining, X-ray microanalysis, and scanning electron microscopy. The higher amount of protein matrix on the Ti scaffold with respect to PLGA and PLGA/HA leads to the conclusion that not only the type of material but the structure significantly affects cell proliferation.